HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP PERILAKU PENCEGAHAN PENYAKIT LEPTOSPIROSIS DI RT 11 RW 01 KELURAHAN CIPEDAK KECAMATAN JAGAKARSA JAKARTA SELATAN - Andini Maharani (2022)
Geographically, Indonesia is an archipelago located at the meeting of four tectonic plates. Indonesia is located in a tropical climate area with two seasons those are summer and wet season. As a result, Indonesia often experiences weather, temperature, and wind direction changes. Flood is the most frequent disaster, particularly in Jakarta. leptospirosis is one of the diseases that occur annually after a flood disaster. The objective of this research was to comprehend whether there was a relationship between knowledge and community attitude toward leptospirosis disease prevention in, Cipedak Jagakarsa, South Jakarta. The design of this research was descriptive analytic with an observational study of cross sectional approach, with an accidental sampling technique. The research sample was residents of Cipedak Jagakarsa Village, South Jakarta, which consisted of 60 respondents. The instrument used was a questionnaire on knowledge level regarding leptospirosis, attitude toward leptospirosis, and leptospirosis prevention behavior. Discussion :The research result described mostly the knowledge of the community of the Cipedak village, on leptospirosis prevention was good (88.3%). Mostly the communities' attitude of Cipedak village, toward leptospirosis prevention was neutral (61.7%). Mostly the communities' action of Cipedak village on leptospirosis prevention was positive (93.3%). There was a relationship between community knowledge toward leptospirosis prevention action with significance value (p) = 0,014. However, there was no relationship between communities' attitudes toward leptospirosis prevention behavior with significance value (p)= 0,106.